The process and principles of intestinal stoma siting - Katarzyna Gaćkowska; Monika Pruchniak; Anna Śmiżewska (Problemy Pielęgniarstwa, 2022)
Intestinal stoma site selection is one of the key elements in preoperative planning and nursing care of patients with intestinal diseases. It is a medical procedure that should be performed prior to any scheduled surgery potentially resulting in a stoma. In emergency surgeries this could be difficult, but an attempt should always be made. Preoperative stoma site selection allows the optimal creation and location of the stoma. The priority is that the stoma should be easily accessible and visible to the patient. A correctly located stoma reduces postoperative complications and improves patients’ quality of life. This work discusses the process and principles of selecting the intestinal stoma site in adult patients prior to scheduled or emergency surgeries. It includes a review of the current literature on this subject. The analysis involved scientific publications from the period between 1 January 2000 and 31 August 2021. Literature searches were conducted in the PubMed and Google Scholar databases, using a mixed combination of the following English and Polish terms: “ostomies”, “intestinal stoma”, “education”, “stoma site selection”, “stoma site marking”, “stoma siting”, “stoma complications”, “peristomal skin complications”, “stomia jelitowa”, “model opieki”, “edukacja”, “wyznaczanie miejsca stomii”, and “powikłania stomijne”. Sixty scientific publications were used to analyse the subject matter of this work.